Characterisation of the Key Aroma Compounds in Black and Green Betel Nuts and Their Aroma Synergy - Yi, Fengping; Luo, Yifu; Wu, Zhenglin; Wu, Kaiwen; Yu, Genfa; Su, Chang; Liao, Shengliang; Zhu, Guangyong (Flavour and fragrance journal, 2025)
Betel nut possesses a distinctive flavour that appeals to specific consumers, despite the well‐documented risks of oral diseases associated with its use. Understanding the characteristic aroma of betel nut is essential for developing appealing substitutes. In this study, supercritical CO 2 fluid extraction was employed to obtain extracts from green and black betel nuts, and the volatile compounds were analysed using headspace solid‐phase microextraction. A total of 30 volatile compounds were identified in green betel nuts and 37 in black betel nuts. Through the odour activity value (OAV) method, 14 key aroma compounds were identified in black betel nuts (FD ≥ 16, OAV ≥ 1). These findings were further validated by aroma reconstitution and omission tests. The aroma synergy of these compounds was also examined using the S‐curve and σ‐τ methods, revealing that smoky compounds significantly masked the perception and intensity of other aroma components. This study provides valuable flavour data for the development of betel nut substitutes, which could contribute to reducing the health risks associated with betel nut consumption.